2020
DOI: 10.1111/gcb.15357
|View full text |Cite
|
Sign up to set email alerts
|

Human activities' fingerprint on multitrophic biodiversity and ecosystem functions across a major river catchment in China

Abstract: Human-induced global change dramatically alters individual aspects of river biodiversity, such as taxonomic, phylogenetic or functional diversity, and is predicted to lead to losses of associated ecosystem functions. Understanding these losses and dependencies are critical to human well-being. Until now, however, most studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(73 citation statements)
references
References 87 publications
2
58
0
Order By: Relevance
“…Since the earliest study published in 2010 [58], there has been a steep growth during the following years in the number of papers published on the theme, with most studies published between 2016 and 2020 (Figure 1). An overview of the studies indicates that metabarcoding-targeting benthic macroinvertebrates have been widely used in ecological assessments in aquatic ecosystems, for example, to assess (1) the effects of contaminants in urbanized, industrialized, and agricultural stream and estuarine areas (e.g., [15,27,39,[58][59][60][61][62][63][64][65]), (2) the effects of stream fragmentation due to dams [66], (3) longterm effects of pesticides [67], oil spills [68], or offshore oil and gas drilling activities [40,69,70], or (4) the effects of invasive species (e.g., invasive algae [71] and crucian carp [72]). It has also proven to be a reliable tool to characterize archive collections of specimens [73], to estimate intraspecific genetic diversity [74], to early detect and monitor invasive species [42,[75][76][77], to be used in the biomonitoring of sea-based fish farms [78,79], and to identify large biogeographic patterns [80,81] and new molecular and cryptic metazoan diversity, in particular in marine ecosystems [55,[81][82][83][84].…”
Section: Progress Of Metabarcoding Studies In Aquatic Bioassessment Using Benthic Macroinvertebratesmentioning
confidence: 99%
See 3 more Smart Citations
“…Since the earliest study published in 2010 [58], there has been a steep growth during the following years in the number of papers published on the theme, with most studies published between 2016 and 2020 (Figure 1). An overview of the studies indicates that metabarcoding-targeting benthic macroinvertebrates have been widely used in ecological assessments in aquatic ecosystems, for example, to assess (1) the effects of contaminants in urbanized, industrialized, and agricultural stream and estuarine areas (e.g., [15,27,39,[58][59][60][61][62][63][64][65]), (2) the effects of stream fragmentation due to dams [66], (3) longterm effects of pesticides [67], oil spills [68], or offshore oil and gas drilling activities [40,69,70], or (4) the effects of invasive species (e.g., invasive algae [71] and crucian carp [72]). It has also proven to be a reliable tool to characterize archive collections of specimens [73], to estimate intraspecific genetic diversity [74], to early detect and monitor invasive species [42,[75][76][77], to be used in the biomonitoring of sea-based fish farms [78,79], and to identify large biogeographic patterns [80,81] and new molecular and cryptic metazoan diversity, in particular in marine ecosystems [55,[81][82][83][84].…”
Section: Progress Of Metabarcoding Studies In Aquatic Bioassessment Using Benthic Macroinvertebratesmentioning
confidence: 99%
“…25%, e.g., [42,56,76,77,82,83,96] and fresh; ca. 21%, e.g., [57,64,65,90,92,119]) (Figure 3). The eDNA, which is extracted directly from environmental matrices, such as water and sediment, tend to be made up of a mix of intra-organismal DNA (e.g., from small organisms) and extra-organismal DNA or trace eDNA shed from large organisms (e.g., body parts, secreted mucus, and feces, tissues, and cells) [30,33,34].…”
Section: Sampling Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Natural habitat loss and fragmentation are important threats to global biodiversity conservation (Chase et al 2020;Sala et al 2000). Studies have shown that the establishment of protected areas (PAs) can effectively curb the destruction of natural ecosystems, and this approach is a major component of biodiversity conservation (Li et al 2020;Ma et al 2012;Tang et al 2011). In 2019, there were 261,200 PAs of various types in the world, covering 15.3% of the global terrestrial and freshwater environment (Maxwell et al 2020).…”
Section: Introductionmentioning
confidence: 99%